DNA probes for distinguishing Psychodopygus wellcomei from Psychodopygus complexus (Diptera: Psychodidae) - P. D. Ready; R. Lainson; J. J. Shaw; A. A. Souza (Memorias do Instituto Oswaldo Cruz, 1991)
Genomic DNA fragments from males of Psychodopygus wellcomei were isolated and shown to be useful as sensitive diagnostic probles for positively separting individuals of this species from those of Ps. complexus. These two members of the Ps. squamiventris series are found sympatrically in foci of cutaneous leishmaniasis in the hill forests of southern Pará State. Of the two species, only Ps. welcomei is thought to be an important vector of Leishmania braziliensis sensu stricto, buth this is based on circumstantial evidence because of the difficulties of identifying female sandflies wothin the series. The diagnostic probes were isolated from a library of Ps. wellcomei built by ligationg short fragments of Sau 3A-resistricted, genomic DNA into the plasmid vector PUC 18. Differential screening of 1316 library clones with total genomic DNA of Ps. Wellcomei and Ps. complexus identified 5 recombinants, with cross-hybridizing inserts of repetitive DNA, that showed strong specificity for Ps. wellcomei. As little as 0.4% of the DNA extracted from an individual sandfly (=ca. 0.5 namograms) was specifically detected. The diagnostic probes were used to identify as Ps. wellcomei a wild-caught female sandfly found infected with L. braziliensis s.s., providing only the second positive association between these two species.